Kadar Hidrasi Kulit Tangan Akibat Penggunaan Hand Sanitizer Dan Cuci Tangan Pada Lansia Penghuni Dua Panti Werdha Jakarta Era Pandemi COVID-19 - Asyer, Aynnie Christabel; Wijayadi, Linda Julianti (Health Information : Jurnal Penelitian, 2023)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Washing hands and using hand sanitizer is one way to prevent it. The use of hand sanitizers and washing hands more frequently causes an increase in Transepidermal Water Loss (TEWL) and a decrease in skin hydration levels. In elderly skin, the epidermal turnover rate and re-epithelialization are reduced, resulting in an increase in TransEpidermal Water Loss (TEWL). This study aims to determine whether or not there is a risk of decreasing skin hydration levels due to the use of hand sanitizers and hand washing and to find out the description of skin hydration based on age, gender and frequency of using hand sanitizers and washing hands in the elderly during the COVID-19 pandemic era. This study is a cross-sectional descriptive study with 94 subjects using a questionnaire and checking skin hydration levels using the SK-IV corneometer. Results: In the study, the average hydration level of the use of hand sanitizer was 10 times 36.4% and the average level of hydration for hand washing was 10 times 35.15%.